TO THE PROBLEM OF FAST READING IN THE ORGANIZATION OF ACADEMIC WORK OF STUDENTS - Victorenko, S. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
The article analyzes the problem of fast reading in the organization of educational work of students. The role of fast reading in the organization of educational work of students and ways of its improvement are determined. The theoretical analysis of this problem is revealed, in particular, attention is paid to the study of methods for improving the academic work of students. It has been found that in order to acquire skills of rapid reading it is appropriate to apply a training that will improve and accelerate the process. It is generalized that fast reading plays a supporting role in the organization of student work and to develop the necessary motivation and daily training for a particular system.
Keywords: fast reading, educational work, students, training, reading, training